2009
DOI: 10.4081/884
|View full text |Cite
|
Sign up to set email alerts
|

Histochemical and ultrastructural study of an elastofibroma dorsi coexisting with a high grade spindle cell sarcoma

Abstract: Elastofibroma dorsi is a pseudotumoral fibroproliferative lesion characterized by polymorphic fiber-like deposits of elastinophilic material. Several theories have been reported explaining the pathogenesis of elastofibroma. Recent cytogenetic studies have demonstrated chromosomal instability in elastofibromas, not normally observed in non-neoplastic tissues. These chromosomal defects are commonly observed in aggressive fibromatosis too. Such clinical observations suggest a multistage pathogenetic mechanism for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Alberghini reported a case having high spindle cell sarcoma together with ED. 20 Therefore, lipoma, hemangioma, and soft tissue sarcoma should be kept in mind for differential diagnosis in cases where there is rapid growth, significant contrast involvement, and atypical location.…”
Section: Discussionmentioning
confidence: 99%
“…Alberghini reported a case having high spindle cell sarcoma together with ED. 20 Therefore, lipoma, hemangioma, and soft tissue sarcoma should be kept in mind for differential diagnosis in cases where there is rapid growth, significant contrast involvement, and atypical location.…”
Section: Discussionmentioning
confidence: 99%
“…There are no results in the literature on tumor size between the right and left sides. 9, 30 It has been reported that surgical treatment can usually be performed for masses larger than ≥5 cm and due to aesthetic concerns. 5 Although the subscapular region is a richly vascularized anatomical region, often at risk of hematoma, complete excision can be easily achieved with healthy surgical margins.…”
Section: Discussionmentioning
confidence: 99%
“…The SUV of these patients were 2.35 and 1.99, respectively. Since no malignant transformation of ELD, except for only one case, was reported of high spindle cell sarcoma and ELD together in the current literature,[ 13 ] we did not perform biopsy in any patient preoperatively.…”
Section: Discussionmentioning
confidence: 99%